2007
DOI: 10.1111/j.1528-1167.2007.01070.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Seizures: Gaps Between the Laboratory and the Clinic

Abstract: Summary: Seizures in neonates (NBs) remain the most frequent neurological problem in the nursery. Considerable debate about their consequences exists between data and deductions reached through animal experimentations and those obtained through clinical investigations. The main conflicting issues are whether seizures in NBs can plant the roots for epileptogenesis and cause long-term deficits. The purpose of this chapter is to evaluate both laboratory and clinical results. Methods: Clinical data will be present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 205 publications
(262 reference statements)
1
25
1
1
Order By: Relevance
“…[14][15][16] Poorer neurodevelopmental outcome has been associated with greater number of seizures per day but usually in the presence of severe neuroanatomical findings. 17 By contrast, in our study, neonatal seizures were usually single events and independent of underlying major structural brain pathology.…”
Section: Original Research Article Discussioncontrasting
confidence: 75%
“…[14][15][16] Poorer neurodevelopmental outcome has been associated with greater number of seizures per day but usually in the presence of severe neuroanatomical findings. 17 By contrast, in our study, neonatal seizures were usually single events and independent of underlying major structural brain pathology.…”
Section: Original Research Article Discussioncontrasting
confidence: 75%
“…Although there is more resistance to acute seizure-induced cell loss than in the adult brain, both clinical (Baram, 2003; Lombroso, 2007) and experimental (Holmes et al, 1998) studies have confirmed that frequent or prolonged seizures lead to long-term impairments in brain development and functional abnormalities. Transient gamma-frequency oscillations (GFOs; > 40Hz) occurring at the onset of most seizures are a marker of a chronic epileptic condition (Worrell et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that neonatal seizures have an increased risk of developing long‐term morbidity, including epilepsy and neurodevelopmental disorders . However, the underlying causes of seizures, rather than seizures per se, have been considered as the critical determinant of neurological abnormalities later in life . While two prior randomized controlled studies found that increasing electrographic seizure burden was significantly associated with severe brain injuries and poor neurodevelopmental outcomes, only term neonates with hypoxic‐ischemic encephalopathy were investigated in the studies.…”
mentioning
confidence: 99%